Unilateral US Withdrawal from the ABM Treaty of 1972 and its Global Consequences - Alexey Sergeevich Butorov (Vestnik RUDN. International Relations, 2016)
The author analyzes the origins and reasons for the termination of the US operations of the Soviet-American ABM Treaty in 1972 based on a study in the Archives of the Russian Federation's foreign policy documents, as well as the US Congress materials, traced the evolutionary path of unilateral withdrawal from the American side agreements. The article notes that for three decades was carried out in relation to the Soviet-American agreements on limiting missile defense systems in 1972 a policy of double standards. Declaring in words their commitment to the fundamental principles of the treaty, in practice, the United States all these years set the stage for a unilateral withdrawal from the contract. Particularly emphasized that the denunciation of Washington in 2001 ABM Treaty is the cornerstone of strategic stability and security in the world, it became the starting point for the deployment of the US global missile defense system.